2012
DOI: 10.1142/s0219455412500411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Two-Parameter Elastic Foundation on the Critical Parameters of Nonhomogeneous Orthotropic Shells

Abstract: A theoretical analysis is presented for determining the free vibrational and buckling characteristics of the nonhomogeneous, orthotropic, thin-walled, circular cylindrical and conical shells under a hydrostatic pressure and resting on a two-parameter elastic foundation. The basic relations have been obtained for the orthotropic truncated conical shell, the Young's moduli and density of which vary continuously in the thickness direction. By applying the Galerkin method, the buckling hydrostatic pressure and dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
(1 reference statement)
0
4
0
4
Order By: Relevance
“…The theoretical and experimental studies have shown that as a result of a number of reasons, elasticity moduli and density of the structural elements may be substantially continuous functions of spatial coordinates [1][2][3]. In this work, based on the publications [4,5], it is assumed that the density and elastic modulus are dependent on the current radius of circular orthotropic plate.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical and experimental studies have shown that as a result of a number of reasons, elasticity moduli and density of the structural elements may be substantially continuous functions of spatial coordinates [1][2][3]. In this work, based on the publications [4,5], it is assumed that the density and elastic modulus are dependent on the current radius of circular orthotropic plate.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
“…In [2,3] the basic equations of the stability of inhomogeneous orthotropic rectangular plates and cylindrical and conical shells without considering the environment resistance are introduced.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
“…Существуют работы [3,6], где показано, что мо-дуль упругости и плотность материала могут зави-сеть от пространственных координат. В данном слу-чае, исходя из работы [3], предполагается, что модуль упругости и плотность зависят только от координаты длины.…”
Section: анализ литературных данных и постановка проблемыunclassified
“…Немаловажным является учет сопротивление внешней среды, который существенным образом зави-сит от природно-климатических условий [6][7][8][9].…”
Section: прикладная механикаunclassified
See 1 more Smart Citation